The Mapping of Honorific Balinese Address Terms Translated into English - Ni Putu Ayu Kartika Dewi; I Wayan Subaker (Hasanuddin University, 2022)
The aim of this article is to find the mapping of Balinese address terms and its translation into English in a Folktale entitled I Juragan Anom. The mapping is used to categories and make clear the major conceptual of the address term are used in folktale I Juragan Anom. Based on the simple analysis, the mapping of Balinese address terms can be categories into three, there are: 1) Balinese address term sub-type indicating honorific: caste system; 2) Balinese address term sub-type personal name system; and 3) Balinese address term sub-type kinship.